Prevalence of and attitudes towards complementary therapy use for weight after breast cancer in Australia: a national survey - Carolyn Ee; Adele Elizabeth Cave; Dhevaksha Naidoo; John Boyages (BMC, 2019)
Abstract Background Weight gain is common after breast cancer (BC) treatment and may increase the risk of disease recurrence. Complementary medicine (CM) use is high amongst BC patients. This paper describes the use of CM from a cross-sectional self-administered survey on prevalence and management of weight after BC. Methods Use of CM was assessed using a question modified from the I-CAM Questionnaire. Participants were asked to rate perceived effectiveness, advantages and disadvantages, and which CM they were willing to use for weight management if there was evidence for effectiveness. The survey was emailed to members of the Breast Cancer Network Australia Survey and Review Group, the largest consumer advocacy group in Australia for people with breast cancer. Results There were a total of 309 responses. Three quarters had used CM in the past 12 months. One third had tried CM for weight loss. Yoga, meditation and pilates were perceived to be effective for weight loss. Perceived advantages of CMs for weight loss were the ability to improve general wellbeing, relaxation, and being non-pharmacological while disadvantages were financial cost, finding a reliable practitioner, and lack of research for effectiveness. Three quarters would be willing to try CM for weight loss if there was evidence for effectiveness, with the most popular CMs being acupuncture, relaxation, yoga, supplements, and meditation. Conclusions The high use of CM in this group is consistent with previous research. Our research suggests that BC survivors would use acupuncture, meditation, supplements and yoga for weight loss if supported by scientifically-credible evidence. Research into the effectiveness of these treatments on weight loss after BC is warranted.